Evaluasi Waktu dan Biaya Proyek Menggunakan Metode Crashing melalui Penambahan Jam Kerja pada Proyek Pembangunan Gedung Diagnostik Terpadu RSUD Sidoarjo - Aziz, M Alfariz Akbar; Triana, Masca Indra; Firmansyah, Mochammad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to evaluate the project’s time and cost using the crashing method This study was conducted to evaluate the time and cost performance of a project using the crashing method by extending daily working hours in the Integrated Diagnostic Building Construction Project at RSUD Sidoarjo. The main purpose of this research is to determine the most efficient combination of project duration and cost while calculating the additional expenses resulting from the application of the crashing method. The data were obtained from project schedules, progress reports, and detailed cost breakdowns for each activity. The analysis began by calculating the normal project duration, then comparing it to the results after applying the crashing method through additional working hours of 1, 2, and 3 hours per day. The results show that the original project duration of 200 days can be shortened to 199 days with an extra hour, to 198 days with two additional hours, and to 197 days with three additional hours per day. The total project costs after crashing were IDR 45,320,447,319.55 for one-hour addition, IDR 45,286,606,288.69 for two-hour addition, and IDR 45,252,907,565.9 for three-hour addition.